Evaluation and Design of Dining Room Chair Based on Analytic Hierarchy Process (AHP) and Fuzzy AHP - Mingbin Liu; Xiurong Zhu; Yanming Chen; Quan Kong (BioResources, 2023)
From the perspective of user needs, a design evaluation system for dining room chairs that can meet user needs was established. Based on the analytic hierarchy process (AHP), the user needs of a dining room chair were quantitatively analyzed by combining qualitative and quantitative methods. Moreover, the comprehensive weight ranking of 14 factors in the object hierarchy was obtained, which provided the design focus and quantitative indexes for designers in the early stage of dining room chair design. Then, in the later stage of dining room chair design, the fuzzy analytic hierarchy process (FAHP) method was used to quantitatively evaluate the three design schemes and obtain the optimal design scheme. The experimental results showed that the user needs evaluation results were positively correlated with the "excellent" grade in the FAHP method. This indicated that the evaluation system realized a symmetry, reliability, and effectiveness between the user needs evaluation and FAHP. Therefore, it can be concluded that this evaluation system based on AHP and FAHP proposed in this study has reliability and validity, and it can be used for design evaluation to judge the popularity of products, enhance the competitiveness of products, and reduce product design costs.